Online Lecture During the COVID-19 Pandemic Affectss Medical Students' Learning Outcomes Based on MCQ Score Examination - Kesuma, Putri; Oktariza, Rury Tiara; rohani, siti; Anggraini, wieke; Indriyani, Indriyani (Syifa'Medika, 2024)
The COVID-19 pandemic has made major changes, one of which is the policy of implementing online lectures from home. This change in method can affect student learning outcomes that can be observed through the results of the MCQ exam at the end of the block. This study was conducted to determine the influence of online lectures during the COVID-19 pandemic on the results of the final MCQ test of student blocks. The retrospective cohort research design was carried out by collecting the MCQ scores at the end of the block at the time before the pandemic, the beginning of the pandemic and the sixth month of the pandemic from students of the 2017, 2018, and 2019 batches and data analysis was carried out by means of the Friedman Test, the Repeated Anova test, the Kruskal-Wallis test and the One-Way Anova. In the class of 2017, the average MCQ test results of the final block before, at the beginning, and in the sixth month of the pandemic were 50.72+8.02 consecutively; 51,39+6,8; 50.31+8.41, and there was no significant difference between them (p>0.001). Meanwhile, in other batches, a significant difference (p<0.001) was found with the results of the final MCQ exam in the 2018 batch of 45.29 + 7.87; 42.77 + 10.4 and 50.68 + 10.63 and for the class of 2019 it is 62.00 + 6.83; 46.8+10.92 and 52.32+10.02. At the beginning of the implementation of online lectures, the final MCQ score of the junior student block was most affected (p<0.001). The online lecture method affects the learning outcomes of first- and second-year students but not for third-year students.